Tax-benefit revealed redistributive preferences over time: Ireland 1987 - 2005 - Olivier Bargain; Claire Keane (University College Dublin, UCD School of Economics, 2010)
By inverting Saez (2002)'s model of optimal income taxation, we characterize the redistributive preferences of the Irish government between 1987 and 2005. The (marginal) social welfare function revealed by this approach is consistently comparable over time and show great stability despite profound changes in market incomes and important fiscal reforms over the period. Results are robust to numerous checks regarding data, income concepts and elasticities. A comparison with the UK shows marked differences reflecting the narrow political spectrum in Ireland compared to radical changes in British politics over the past 30 years. Some anomalies in the revealed social welfare function suggests introducing transfers to the working poor.
hdl:10197/2667
Keywords: C63; C81; D31; D63; H11; H21; H23; H31; 330; Social preferences; Optimal taxation; Labour supply